Social determinants of health : an interdisciplinary approach to social inequality and well-being - Bonner, Adrian (Policy Press, 2018)
This book provides an applied, interdisciplinary approach to an understanding of the key social determinants of health, essential at a time of increasing inequalities and reductions in existing NHS services and local authority budgets. A person's health and wellbeing is influenced by a spectrum of socioeconomic, cultural, living and working conditions, social and community networks and lifestyle choices. Based on the 'rainbow model' of the social determinants of health, chapters from experts in a wide range of disciplines examine the key factors which can lead to poor quality of life, homelessness and reduced mortality. Featuring practitioner, academic and commentator experiences, and clear case studies, this book will enable researchers, front-line workers, managers, service commissioners and politicians to identify and employ the most appropriate health, social and economic interventions to support those at the edge of the community, and the promotion of their inclusion in society.